The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41559-019-1062-4
|View full text |Cite|
|
Sign up to set email alerts
|

Phenological shifts alter the seasonal structure of pollinator assemblages in Europe

Abstract: Pollinators play an important role in terrestrial ecosystems by providing key ecosystem functions and services to wild plants and crops, respectively. The sustainable provision of such ecosystem functions and services requires diverse pollinator communities over the season. Despite evidence that climate warming shifts pollinator phenology, a general assessment of these shifts and their consequences on pollinator assemblages is still lacking. By analyzing phenological shifts of over 2000 species, we show that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 42 publications
5
58
0
Order By: Relevance
“…Most of the studies showed a simultaneous advance in the phenology of pollinators and plants over the studied period in parallel with increasing average temperatures, but alternative patterns (i.e. simultaneous delays or opposite shifts) have also been described [25,26]. Mismatches between the emergence of bee species and the blooming of their main resources have been specifically recorded [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies showed a simultaneous advance in the phenology of pollinators and plants over the studied period in parallel with increasing average temperatures, but alternative patterns (i.e. simultaneous delays or opposite shifts) have also been described [25,26]. Mismatches between the emergence of bee species and the blooming of their main resources have been specifically recorded [26].…”
Section: Introductionmentioning
confidence: 99%
“…Many phenological shifts have already been reported at the species level for the insect emergence (e.g. [24,25]) or blooming time of flowering plants (e.g. [13]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, empirical estimations show an average advance of 11.5 days in 120 349 years (roughly 1 day per decade) for appearance of pollinators, and 9.5 days for plant 350 flowering in America [13]. Likewise, estimates for European pollinators suggest an 351 average phenological advancement of 6 days in 60 years (1 day per decade) [43]. Such predict an abrupt increase in extinction rates.…”
mentioning
confidence: 99%
“…Likewise, [48] showed that early flowering produced lower pollination success and observed in some real life systems [43,52]. Additionally, between-community variability 380 in responses to phenological shifts poses the questions about which are the chief 381 determinants of these differences, species traits or connectivity patterns.…”
mentioning
confidence: 99%